A spectral expansion approach for geodetic slip inversion: implications for the downdip rupture limits of oceanic and continental megathrust earthquakes. Issue 1 (22nd September 2017) - Xu, Xiaohua; Sandwell, David T; Bassett, Dan
SUMMARY: We have developed a data-driven spectral expansion inversion method to place bounds on the downdip rupture depth of large megathrust earthquakes having good InSAR and GPS coverage. This inverse theory approach is used to establish the set of models that are consistent with the observations. In addition, the inverse theory method demonstrates that the spatial resolution of the slip models depends on two factors, the spatial coverage and accuracy of the surface deformation measurements, and the slip depth. Application of this method to the 2010 M w 8.8 Maule Earthquake shows a slip maximum at 19 km depth tapering to zero at ∼40 km depth. In contrast, the continent–continent megathrust earthquakes of the Himalayas, for example 2015 M w 7.8 Gorkha Earthquake, shows a slip maximum at 9 km depth tapering to zero at ∼18 km depth. The main question is why is the maximum slip depth of the continental megathrust earthquake only 50 per cent of that observed in oceanic megathrust earthquakes. To understand this difference, we have developed a simple 1-D heat conduction model that includes the effects of uplift and surface erosion. The relatively low erosion rates above the ocean megathrust results in a geotherm where the 450–600 °C transition is centred at ∼40 km depth. In contrast, the relatively high average erosion rates in the Himalayas of ∼1 mm yr –1 results in a geotherm where the 450–600 °C transition is centred at ∼20 km. Based on these new observations and models, we suggest that the effect of erosion rate on temperature explains the difference in the maximum depth of the seismogenic zone between Chile and the Himalayas.